Integrated Transcriptome and Microbiota Reveal the Regulatory Effect of 25-Hydroxyvitamin D Supplementation in Antler Growth of Sika Deer - Huazhe Si; Songze Li; Weixiao Nan; Jianan Sang; Chao Xu; Zhipeng Li (Animals, 2022)
The level of plasma 25-hydroxyvitamin D (25(OH)D) is associated with the growth of the antler, a fast-growing bone organ of Cervidae. However, the benefits of 25(OH)D supplementation on antler growth and the underlying mechanisms remain unclear. Here, the antler growth profile and transcriptome, plasma parameters, rumen bacteria, and metabolites (volatile fatty acids and amino acids) were determined in sika deer in a 25(OH)D supplementation group (25(OH)D, n = 8) and a control group (Ctrl, n = 8). 25(OH)D supplementation significantly increased the antler weight and growth rate. The levels of IGF-1,25(OH)D and 1,25-dihydroxyvitamin D were significantly higher in the 25(OH)D group than in the Ctrl group, while the levels of LDL-C were lower. The levels of valerate and branched-chain amino acids in the rumen fluid were significantly different between the 25(OH)D and Ctrl groups. The bacterial diversity indices were not significantly different between the two groups. However, the relative abundances of the butyrate-producing bacteria (families Lachnospiraceae and Succinivibrionaceae) and the pyruvate metabolism pathway were higher in the 25(OH)D group. The transcriptomic profile of the antler was significantly different between the 25(OH)D and Ctrl groups, with 356 up- and 668 down-regulated differentially expressed genes (DEGs) in the 25(OH)D group. The up-regulated DEGs were enriched in the proteinaceous extracellular matrix and collagen, while the down-regulated DEGs were enriched in the immune system and lipid metabolism pathways. Overall, these results provide novel insights into the effects of 25(OH)D supplementation on the host metabolism, rumen microbiota, and antler transcriptome of sika deer.